Aboriginal Peoples Survey, 2012 [Canada] [Excel] ... - Social And Aboriginal Statistics Division (Borealis, 2016)
The 2012 Aboriginal Peoples Survey (APS) is a national survey of First Nations people living off reserve, Métis and Inuit aged six years and over. The 2012 APS represents the fourth cycle of the survey. It was designed to be thematic; questions emphasize education and employment, with a health supplement. It also collects information on language, income, housing and mobility.The APS complements other sources of information, including the Canadian Census of Population and the National H ousehold Survey (NHS). Following the release of data from the 2006 APS, a content review was conducted to ensure the future relevance of existing APS questions to key stakeholders and to identify any potential data gaps. The review brought together expertise from a diverse group of researchers and subject matter experts, both from within and outside of Statistics Canada. New survey questions were developed and added to the 2012 APS questionnaire in order to place greater emphasis on the t hemes of education and employment, in ... : Version Date: 2013-11-25Version Text: 1 ...